Model Development of a Hybrid Battery–Piezoelectric Fiber System Based on a New Control Method - Hesarian, Mir Saeid; Tavoosi, Jafar; Alanazi, Tarek I. (Polymers, 2022)
By increasing the application of smart wearables, their electrical energy supply has drawn great attention in the past decade. Sources such as the human body and its motion can produce electrical power as renewable energy using piezoelectric yarns. During the last decade, the development of the piezoelectric fibers used in smart clothes has increased for energy-harvesting applications. Therefore, the energy harvesting from piezoelectric yarns and saving process is an important subject. For this purpose, a new control system was developed based on the combination of the sliding mode and particle swarm optimization (PSO). Using this method, due to the piezoelectric yarn cyclic deformation process, electrical power is produced. This power is considered the input voltage to the controlling system modeled in this article. This system supplies constant voltage to be saved in a battery. The battery supplies power for the electrical elements of smart fabric structure for different applications, such as health care. It is shown that the presence of PSO led to the improvement of system response and error reduction by more than 30%.